Multi-slice ultrasound image calibration of an intelligent skin-marker for soft tissue artefact compensation. (6th September 2017) - Masum, M.A.; Pickering, M.R.; Lambert, A.J.; Scarvell, J.M.; Smith, P.N.
Abstract: In this paper, a novel multi-slice ultrasound (US) image calibration of an intelligent skin-marker used for soft tissue artefact compensation is proposed to align and orient image slices in an exact H-shaped pattern. Multi-slice calibration is complex, however, in the proposed method, a phantom based visual alignment followed by transform parameters estimation greatly reduces the complexity and provides sufficient accuracy. In this approach, the Hough Transform (HT) is used to further enhance the image features which originate from the image feature enhancing elements integrated into the physical phantom model, thus reducing feature detection uncertainty. In this framework, slice by slice image alignment and calibration are carried out and this provides manual ease and convenience.